The relationship of complete denture patient's satisfaction level with quality of life at Hasanuddin University Teaching Dental Hospital : Hubungan tingkat kepuasan pengguna gigi tiruan lengkap terhadap kualitas hidup pasien di Rumah Sakit Gigi Mulut Pendidikan Universitas Hasanuddın - Mirna, Andi Mirna Nasliah; Mude, Acing Habibie; Habar, Ike; Jubhari, Eri Hendra; Machmud , Edy (Makassar Dental Journal, 2024)
A problem in complete denture (CD) treatment is the patient's ability to use and adapt to the denture. If not resolved properly, the denture is considered unsatisfactory by the patient and has an impact on oral health and quality of life. This study provides a des-cription of the quality of life of CD users with flabby ridge on the level of patient satisfaction with speech function, chewing, appear-ance, and comfort using a denture. Analytical observational research with a cross-sectional design was conducted using the me-thod of direct examination and interview using a questionnaire. Based on age group, there is a significant relationship (p<0.05) between the age group of 51-60 years and the age group of 61-70 years with patient satisfaction in the mastication dimension and the overall OHIP-14 dimension obtained a mean value of 16.82 with SD 0.75. It was concluded that the quality of life of CD users with flabby ridge was good; overall the study subjects were satisfied with their dentures